Examining School Principals’ Conceptions of Assessment and Grading Practices - Cheng, Liying; Baidoo-Anu, David; DeLuca, Christopher (Alberta Journal of Educational Research, 2023)
Principals play a key leadership role in school effectiveness and student success; however, one area that has received relatively little attention so far is principals’ embedded understanding of assessment and grading within the educational context where they work. We examined 141 Chinese school principals’ conceptions of assessment and grading practices using a survey research design. Our results indicated that principals viewed summative assessment as necessarily serving two purposes: (a) accountability, and (b) improvement of teaching and learning. Assessment that does not serve these dual purposes was not viewed as maximally supporting learning in this educational context. The study further found that accountability pressures influenced principals’ conceptions of assessment and consequently shaped their approaches to grading in China’s examination-oriented culture. This study provides implications for a heightened understanding of principals’ leadership in the crucial role that student assessment plays in both enhancing instruction and student learning and ever-expanding accountability mandates within the Chinese education context and other educational contexts globally. Keywords: principals, conceptions of assessment, grading practices, China. Les directeurs d'école jouent un rôle clé dans l'efficacité de l'école et la réussite des élèves. Cependant, un domaine qui a reçu relativement peu d'attention jusqu'à présent est la compréhension de l'évaluation et de la notation par les directeurs dans le contexte éducatif où ils travaillent. À l'aide d'une enquête, nous avons examiné les conceptions de 141 directeurs d'école chinois sur les pratiques d'évaluation et de notation. Nos résultats indiquent que les directeurs d'école considèrent que l'évaluation sommative doit nécessairement servir deux objectifs : (a) la responsabilité et (b) l'amélioration de l'enseignement et de l'apprentissage. L'évaluation qui ne sert pas ces deux objectifs n'est pas considérée comme un soutien maximal à l'apprentissage dans ce contexte éducatif. L'étude a également révélé que les pressions liées à l'obligation de rendre des comptes ont influencé les conceptions des directeurs d'école en matière d'évaluation et, par conséquent, leurs approches de la notation dans la culture chinoise axée sur les examens. Cette étude a des implications pour une meilleure compréhension du leadership des directeurs d'école en ce qui concerne le rôle crucial que joue l'évaluation des élèves dans l'amélioration de l'enseignement et de l'apprentissage des élèves, ainsi que des mandats de responsabilisation toujours plus étendus dans le contexte éducatif chinois et d'autres contextes éducatifs dans le monde. Mots clés : directeurs d'école, conceptions de l'évaluation, pratiques de notation, Chine.